Exploring Zakat Entities And Their Functions In Bangladesh: A Comprehensive Overview And Prospective Pathways For Amplification - Monir, Moniruzzaman (Center of Strategic Studies (PUSKAS) BAZNAS, 2024)
An outline of the function and impact of Zakat organizations in Bangladesh is provided in this study. Zakat, a fundamental component of Islamic finance, is essential for combating poverty and advancing social welfare in nations where Muslims predominate, like Bangladesh. The study provides an overview of the primary roles that Zakat institutions play in Bangladesh through targeted analysis, including the collecting, distributing, and use of Zakat funds. It draws attention to how these organizations help underprivileged populations, combat poverty, and promote socioeconomic growth. The study provides potential pathways for Zakat institutions, from international exchange and collaboration initiatives to community empowerment programs. Zakat institutions may enhance their impact on reducing poverty, social well-being, and a sustainable development approach in Bangladesh by adopting these prospective paths. This research intends to stimulate transformational action and policy changes, encouraging more equitable and viable Zakat management practices in Bangladesh, with an emphasis on revealing the untapped strengths of Zakat institutions and suggesting several alternatives for their betterment.